A Bibliometric Analysis of Open Government: Study on Indonesia and Philippines - Umi Kulsum; Achmad Nurmandi; Isnaini Muallidin; Mohammad Jafar Loilatu; Danang Kurniawan (Journal of Governance, 2022)
This study aims to analyze the implementation of Open Government in Indonesia and the Philippines, where the two countries were part of the founders of the Declaration of Open Government from Southeast Asian countries. In the era of all-technology, the demand for improving the quality of government services is very much needed, given the existence of information technology that can be adopted in governance. So that the request for easy public access in supervising the performance of the Government as well as to combat acts of corruption committed by the Government is an obligation that the Government must fulfill. This writing uses a literature review from 329 journals. These journals were obtained from Scopus, then downloaded in RIS format. After that, the RIS file is processed in the Vosviewer software. The results of the Vosviewer become a reference in analyzing the data presented regarding Open Government. The results of this study indicate that responding to Open Government requires government data that is transparent, democratic, and the participation of citizens to control and monitor whether the state has implemented open data or not.